Unveiling singlet oxygen spin trapping in catalytic oxidation processes using in situ kinetic EPR analysis - Wu, Jing-Hang; Chen, Fei; Yang, Tian-Hao; Yu, Han-Qing (Proceedings of the National Academy of Sciences - PNAS, 2023)
Singlet oxygen ( O ) plays a pivotal role in numerous catalytic oxidation processes utilized in water purification and chemical synthesis. The spin-trapping method based on electron paramagnetic resonance (EPR) analysis is commonly employed for O detection. However, it is often limited to time-independent acquisition. Recent studies have raised questions about the reliability of the O trapper, 2,2,6,6-tetramethylpiperidine (TEMP), in various systems. In this study, we introduce a comprehensive, kinetic examination to monitor the spin-trapping process in EPR analysis. The EPR intensity of the trapping product was used as a quantitative measurement to evaluate the concentration of O in aqueous systems. This in situ kinetic study was successfully applied to a classical photocatalytic system with exceptional accuracy. Furthermore, we demonstrated the feasibility of our approach in more intricate O -driven catalytic oxidation processes for water decontamination and elucidated the molecular mechanism of direct TEMP oxidation. This method can avoid the false-positive results associated with the conventional 2D O detection techniques, and provide insights into the reaction mechanisms in O -dominated catalytic oxidation processes. This work underscores the necessity of kinetic studies for spin-trapping EPR analysis, presenting an avenue for a comprehensive exploration of the mechanisms governing catalytic oxidation processes.